Patient with bipolar I disorder who presented with low blood lithium levels after receiving crushed tablets via a nasogastric tube: A case report - Fujikawa, Ryoko; Fujii, Kumiko; Ozeki, Yuji (Frontiers in Psychiatry, 2022)
In clinical psychiatric cases, the placement of a nasogastric tube is occasionally considered. If a patient who presents with mania or other psychiatric conditions refuses to take drugs, they are administered via the nasogastric tube. The tablet is crushed, suspended, passed via the nasogastric line, and reaches the stomach directly. However, the effects of these processes on blood drug concentrations remain unclear. Herein, we report a patient with bipolar I disorder who presented with low blood lithium carbonate (Li) concentrations after receiving the drug via the nasogastric tube. Case A 26-year-old woman developed manic symptoms with grandeur delusion. She was admitted to a psychiatric hospital three times after diagnosis. Her manic symptoms with delusion improved with Li and aripiprazole(ARP). Her condition stabilized with Li 800 mg/day and ARP 9 mg/day. After the Li dose was reduced to 600mg/day, she maintained remission, with the blood level range of Li being 0.31～0.42mEq/L. After one year, she was admitted to our hospital due to a jaw deformity. During the perioperative period, treatment with oral Li was discontinued by the surgeons, and her manic symptoms recurred. During therapy with olanzapine 20 mg and Li 800 mg, her blood Li concentration was 0.67 mEq/L. The symptoms remained. Hence, the Li dose increased to 1000 mg/day. However, she refused to take the medication. Thus, a nasogastric tube was used to administer medicines. Thereafter, the blood Li concentration decreased to 0.43 mEq/L, which was lesser than 800 mg/day. Each blood sample was collected approximately 18 h after the administration. Her symptoms remained. Thereafter, she agreed to take the medication, and the Li concentration reached 0.78 mEq/L. Then, the symptoms partly improved. Conclusion After the administration of Li via the nasogastric tube, the Li concentration decreased, which was lower than expected. This phenomenon could be attributed to the fact that the medication was crushed, suspended, and administered via the nasogastric tube. Therefore, pulverizing and administering Li tablets via the nasogastric tube can be applied for the management of mania, however caution should be observed because of the risk of fluctuations in blood Li levels, as in this case.